User participation in watershed management and research - Johnson, Nancy L.; Ravnborg, Helle Munk; Westermann, Olaf; Probst, Kirsten (International Food Policy Research Institute, 2001)
Many watershed development projects around the world have performed poorly because they failed to take into account the needs, constraints, and practices of local people. Participatory watershed management -in which users help to define problems, set priorities, select technologies and policies, and monitor and evaluate impacts -is expected to improve performance. User participation in watershed management raises new questions for watershed research, including how to design appropriate mechanisms for organizing stakeholders and facilitating collective action. Management of a complex system such as a watershed may also require user participation in the research process itself. An increasing number of watershed research projects are already participatory, however challenges remain to institutionalizing user participation in both watershed management and research.